Crowd Funding as a Tool for Financing the Construction of Social Facilities - Ptashchenko, Liana; Chechelashvili, Maya (International Journal of Engineering and Technology, 2018)
The article analyzes the social state of countries experiencing economic convergence in the European Community on the basis of rating indicators of the level of happiness of the population. It is noted that the main problem of weak socialization in these countries is inadequate financing of measures for implementing me general social policy, including construction of social facilities. The article substantiates the idea that it is possible to solve the problem of financing the construction of social facilities with the help of crowd funding, which is not popular in this industry yet. Based on the study of crowd funding, the purpose of the article is to determine the organizational mechanism for the successful implementation of social projects with the help of crowd-hosting platforms. Since the basis of crowded platforms development in the social sphere is trust and motivation, the article suggests using crowd-sourcing, which would help a wider circle of the public pay attention to the social project.The authors are the first to form an organizational mechanism for supporting and implementing projects for the construction of social facilities with the help of crowd-funding platforms and proposed a mixed technology for implementing a social project; this technology is an advanced combination of creating experimental objects and active implementation of projects through advertising and crowd-sourcing. The support for the project on the crowd-diving platform was described by the authors as crowd-shipping development. The emphasis was placed on the need to train active and enterprising people in technologies and prospects of crowd finding for projects of construction of social facilities, as well as the population awareness of crowd funding advantages and possibilities for the development of regions (territories) of the country. It is noted that this will allow creating objective conditions for the formation of citizens' attitudes towards the socialization of relations in society, envolving the population into social activity, and forming a social culture in society.Â
Keywords: construction of social facilities; crowd funding; crowd funding project; crowd sourcing; development; technology implementation of social projects.